A proposed role for diffusible signal factors in the biofilm formation and morphological transformation of Helicobacter pylori - Pawel Krzyzek,; Grazyna Gosciniak, (Turkish Journal of Gastroenterology, 2019)
Due to the increasing resistance of Helicobacter pylori to antibiotics, there is a growing need for new strategies for the effective eradication of this pathogen. The inhibition of quorum-sensing activity in most microorganisms leads to a decrease in virulence. A different reaction is observed in H. pylori, as interfering with the production of autoinducer-2 initiates biofilm formation and increases the survival of these bacteria. Therefore, it is believed that there is an alternative way to control the physiological changes of H. pylori exposed to environmental stress. In this article, we present the compounds probably involved in the modulation of H. pylori virulence. Diffusible signal factors (DSFs) are fatty acid signal molecules involved in communication between microbes. DSFs are likely to stimulate H. pylori transition into a sedentary state that correlates with bacterial transformation into a more resistant coccoid form and initiates biofilm formation. Biofilm is a structure that plays a crucial role in protecting against adverse environmental factors (low pH, oxidative stress, action of immune system) and limiting the effective concentration of antimicrobial substances. This article has suggested and characterized the existence of an alternative DSF-mediated cell-cell signaling of H. pylori, which controls autoaggregative behaviors, biofilm formation, and the transition of microorganisms into the coccoid form.Cite this article as: Krzyżek P, Gościniak G. A proposed role for diffusible signal factors in the biofilm formation and morphological transformation of Helicobacter pylori. Turk J Gastroenterol 2018; 29: 7-12.